Optimized Ultrasound-Assisted Peracetic acid pretreatment approach for enhanced sugars and decreased inhibitors for bio-ethanol production from OPEFB - Poludasu, Ramamohan; Piyarat, Boonsawang; Benjamas, Cheirsilp (Vietnam Journal of Science and Technology, 2024)
The Oil palm empty fruit bunch (OPEFB) constitutes the primary solid waste produced by the palm oil sector. This study aims to identify the best pretreatment conditions for increasing the sugars yield and lowering that of inhibitors in ultrasonic-treated OPEFB biomass using PAA. To study the individual and combined effects of pretreatment independent process variables, such as PAA concentration, sonication time, and temperature on the response variables glucose, xylose, arabinose, furfural, and HMF response surface approach, the central composite design (CCD) model was used. According to the findings from response surface analysis, the optimal conditions to obtain the highest sugar yield with the least amount of inhibitors were PAA concentration (10%), sonication time (120 min), and temperature (60ºC) for pretreatment, which produced 32.19, 15.83, and 5.92 g/L of glucose, xylose, and arabinose sugars, respectively, and about 1.86 and 3.2 g/L of furfural and HMF, respectively. The strong agreement observed between the experimental and predicted results. Detoxification with activated carbon, results in decreasing the inhibitory compounds in the hydrolysate. Subsequent fermentation studies demonstrated that hydrolysate with higher sugar content resulted in achieving a greater ethanol yield (67.5 g/L) than low ultrasonicated OPEFB (56.7 g/L).